Planning & Steering of automotive dealers and the influence of the OEM - Kallookaran, Roberto; Pichanič, Mikuláš, 1942-; Malý, Josef, 1958-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
Our research purpose is to show that the generic strategy choice, differentiation or cost leadership, of the automotive manufacturer has an influence on the corporation between him and his dealers. To prove our assumption we formulate three hypotheses where we investigate how targets are determined between dealer and manufacturer, how the dealer understands the strategy of the manufacturer and how the dealer perceives consultation services provided from the manufacturer. For our research we collected empirical data via an online survey at the dealer side. The evaluation of our results is finally based on 71 valid dealer responses from Germany. Our findings show a significant dependency between the manufacturer's choice of strategy and the investigated objects. We argue that customer expectations regarding service quality and the perception on, how they connect dealer with the brand, are the main reasons why manufacturers following differentiation strategy apply a more corporative target determination approach than manufactures persuading a cost leadership strategy. Subsequently we see that, dealers affiliated with manufacturers following differentiation strategy have a better understanding of the manufacturer's strategy and a better opinion about profitability consultation
Vedoucí práce: Mikuláš Pichanič
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2010
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations